Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0954411916651461
|View full text |Cite
|
Sign up to set email alerts
|

Influence of third-body particles originating from bone void fillers on the wear of ultra-high-molecular-weight polyethylene

Abstract: Calcium sulfate bone void fillers are increasingly being used for dead space management in infected arthroplasty revision surgery. The presence of these materials as loose beads close to the bearing surfaces of joint replacements gives the potential for them to enter the joint becoming trapped between the articulating surfaces; the resulting damage to cobalt chrome counterfaces and the subsequent wear of ultra-high-molecular-weight polyethylene is unknown. In this study, third-body damage to cobalt chrome coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…A clinical concern with using resorbable mineral beads to treat PJI is third body wear of articulating surfaces. While we did find one report of third body wear in six patients associated with hydroxy apatite acetabular cup coating, in vitro tribological and hip simulator testing suggest that calcium sulfate has the potential to be used as an antibiotic carrier, without resulting in excessive third body wear . Another concern associated with localized antibiotic therapy is that of the development of antibiotic resistance if the infecting bacteria are exposed to sub‐MIC concentrations for prolonged periods.…”
Section: Discussionmentioning
confidence: 83%
“…A clinical concern with using resorbable mineral beads to treat PJI is third body wear of articulating surfaces. While we did find one report of third body wear in six patients associated with hydroxy apatite acetabular cup coating, in vitro tribological and hip simulator testing suggest that calcium sulfate has the potential to be used as an antibiotic carrier, without resulting in excessive third body wear . Another concern associated with localized antibiotic therapy is that of the development of antibiotic resistance if the infecting bacteria are exposed to sub‐MIC concentrations for prolonged periods.…”
Section: Discussionmentioning
confidence: 83%
“…Medical-grade calcium sulphate, for example, is derived from earth-sourced gypsum rock and is a relatively soft material with a value of 2 on the Mohs scale. 36 However, it may contain insoluble and potentially harder impurities such as quartz (7 on the Mohs scale) 36 or slower-absorbing calcium phosphate constituents that may have an influence on the wear of UHMWPE, 21 meaning that the findings from this study do not translate directly to all bone void filler materials.…”
Section: Discussionmentioning
confidence: 93%
“…19 The influence of calcium sulphate on third-body wear has been previously investigated in the hip 20 and in simple geometry pin-on-plate/pin-on-disc studies. 21,22 In all studies, calcium sulphate did not scratch the surface of CoCr counterfaces with a lip height of sufficient magnitude to influence polyethylene wear rate. The hip simulation study, however, showed an elevated wear rate while calcium sulphate was present in the lubricant.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations